Land Governance, Gender Equality and Development: Past Achievements and Remaining Challenges. (9th March 2016) - Ravnborg, Helle Munk; Spichiger, Rachel; Broegaard, Rikke Brandt; Pedersen, Rasmus Hundsbæk
Abstract: Most land governance reforms seek to enhance tenure security, encourage investments and thereby promote economic growth. Increasingly, land reforms attempt to secure women's and other vulnerable groups' access to land. This article reviews the extent to which gender equality in land tenure has been pursued in these reforms and examines the role played by donor cooperation. Despite significant progress in developing land legislation that upholds gender equality, implementation often does not follow suit, and women still face discrimination. Based on country case studies, the article identifies six challenges, which should be addressed to achieve gender equality in land tenure. © 2016 UNU‐WIDER. Journal of International Development published by John Wiley & Sons, Ltd.